2020
DOI: 10.12973/eu-jer.9.3.1257
|View full text |Cite
|
Sign up to set email alerts
|

HOTSEP: Revised Anderson’s Taxonomy in Environmental Learning of COVID-19

Abstract: Environmental learning in the 21st century requires a high level of thinking ability, especially to solve environmental problems when COVID-19 pandemic. This was to develop a new level of thinking, namely Higher Order Thinking Skills of Environmental Problem (HOTSEP) which is a revision of Anderson's Taxonomy. The purpose of this study was to measure students HOTSEP in the context of environmental problems related to COVID-19. The research method used in this research was descriptive. The sample used 277 unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
22
0
3
Order By: Relevance
“…Such learning tools must be in accordance with students' cognitive development. [23][24][25][26] A low HOTS score may have an impact on the difficulty of generating quick decision-making or solutions in unpredictable situations during COVID-19. Hence, development of tools, such as e-books, worksheets, and teaching materials becomes an important policy measure.…”
Section: Resultsmentioning
confidence: 99%
“…Such learning tools must be in accordance with students' cognitive development. [23][24][25][26] A low HOTS score may have an impact on the difficulty of generating quick decision-making or solutions in unpredictable situations during COVID-19. Hence, development of tools, such as e-books, worksheets, and teaching materials becomes an important policy measure.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental problems that must be solved require Higher Order Thinking Skills (HOTS). This is because HOTS ability enables students to analyze problems, then evaluate the problem and create solutions to these problems [9][10][11][12][13]. Environmental problems are becoming more complex due to the COVID-19 pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…The research that has been done in previous research is related to the description of the student's HOTS score. The results showed that the students' HOTS scores are still in the low category [9]. Besides, various learning models and strategies have been developed that aim to increase HOTS [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive process dimension is divided into remembering, understanding, applying, analyzing, evaluating, and creating. Concerning environmental science which is one of the studies of biology, Ichsan & Rahmayanti (2020) provides a view that the dimensions of analyzing, evaluating, and creating are associated with the ability to criticize, solve environmental problems, and develop innovations about the environment. Meanwhile, Harvey et al (2019) in emotion-cognition taxonomy explains that the level of cognition includes the ability to describe, understand, construct, and perform critical analysis.…”
Section: Introductionmentioning
confidence: 99%